2009
DOI: 10.1007/s10646-009-0371-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selected heavy metals (Pb, Cu, Ni, and Cd) in the aquatic medium on the restoration potential and accumulation in the stem cuttings of the terrestrial plant, Talinum triangulare Linn

Abstract: The heavy metal (Cu, Pb, Ni, and Cd) accumulation capacity of the stem cuttings of the terrestrial, ornamental plant, Talinum triangulare was assessed in hydroponic medium. The stem cuttings of T. triangulare, grew well in distilled water regenerating roots and aerial parts. On exposure to various concentrations of Cu, Pb, Ni, and Cd, a concentration dependent decrease was observed in the number of leaves produced and roots regenerated and an increase in the number of days required for the initiation of roots.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 47 publications
3
7
0
2
Order By: Relevance
“…For example, results of the hydroponic studies conducted by Benzarti et al (2008) showed that the BCF of four plants decreased as the Cu concentration in solution increased from 1 to 1000 lM. A similar tendency was also observed for the terrestrial plant T. triangulare when it was exposed to various concentrations of waterborne Cu (Rajkumar et al 2009). In the present study, the BCF of switchgrass was calculated as 503, 341, 154, and 102, with Cu concentrations in solution of 0.5, 1.0, 2.0, and 5.0 lg mL -1 , respectively.…”
Section: Bioaccumulation Kinetics Of Cu To Switchgrasssupporting
confidence: 53%
“…For example, results of the hydroponic studies conducted by Benzarti et al (2008) showed that the BCF of four plants decreased as the Cu concentration in solution increased from 1 to 1000 lM. A similar tendency was also observed for the terrestrial plant T. triangulare when it was exposed to various concentrations of waterborne Cu (Rajkumar et al 2009). In the present study, the BCF of switchgrass was calculated as 503, 341, 154, and 102, with Cu concentrations in solution of 0.5, 1.0, 2.0, and 5.0 lg mL -1 , respectively.…”
Section: Bioaccumulation Kinetics Of Cu To Switchgrasssupporting
confidence: 53%
“…Selection of plant species for metal removal is based on the plants which should have high tolerance to the contaminant and high capacity accumulation rate for the element and capability to accumulate several metals (Rajkumar et al, 2009). Ceratophyllum demersum is a submerged aquatic macrophyte belonging to Ceratophyllaceae family (Arber, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…heavy metals) from polluted mediums (Rai 2009;Susarla et al 2002). Selection of plant species for metal removal is based on the known of the tolerance and capacity accumulation of the species (Rajkumar et al 2009). For the good accumulation of metals, plants should have some of the following traits: (a) high tolerance to the contaminant, (b) high accumulation rate for the element, (c) capability to absorb high levels of contaminants, (d) capability to accumulate several metals, (e) high biomass production and (f) resistance to diseases and pests (Wanatabe 1997).…”
Section: Introductionmentioning
confidence: 99%